Spatial distribution of vermetids (Mollusca: Gastropoda) in the Rocas Atoll, Equatorial South Atlantic - Soares, Marcelo de Oliveira; Meirelles, Carlos Augusto Oliveira de; Lemos, Valesca Brasil (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2010)
The Rocas Atoll is a biogenic reef located 266 km from the brazilian northeast coast. Its carbonate structure is formed by corals, calcareous algae, foraminifers and vermetids. Such studied vermetid species are indicators of the sea level and of intertidal or immediately subtidal paleoenvironments, being able to contribute to elucidate the geological history of the only atoll of the South Atlantic. Despite its importance as bioconstructors, there are few studies on the systematics and distribution of these mollusks in this oceanic reef system. Data was obtained on the species, density and distribution leeward and windward from the encrusting taphocoenosis. The species Dendropoma irregulare (d’Orbigny, 1842) and Petaloconchus varians (d’Orbigny, 1841) were recognized in different sectors of the reef system, mainly in the windward sector (0,26 ± 0,04 ind/cm2 century). In the wave-dominated side of the depositional system occur a lower bioaccumulation of the fossilized shells (0,11 ± 0,02 ind/cm2 century).